Chickpea : crop wild relatives for enhancing genetic gains - Singh, Mohar (Academic Press, 2020)
Chickpea: Crop Wild Relatives for Enhancing Genetic Gains explores aspects related to critical analysis on factors responsible for narrow genetic base of chickpea productions including domestication bottleneck, the level of diversity present in different cultivated and wild species, the uniqueness and usefulness of potential gene sources available and maintained in production systems across the globe, the level of genetic erosion both at landrace and species level over time and space etc. Despite considerable international investment in conventional breeding, production of chickpea has not yet been significantly improved beyond that achieved through its normal single domestication event and high self-pollination rate. Total annual pulse production of ~12 million tons (FAO 2016) is far below actual potential. Susceptibility to both biotic and abiotic stresses have created a production level bottleneck whose solution possibly lies in the use of crop wild relatives and other genetic traits cultivated by tailoring novel germplasm. Presenting options for widening the genetic base of chickpea cultivars by introgression of diverse genes available in distantly related wild Cicer taxa, thus expanding the genetic base and maximize genetic gains from the selection, it is necessary to accumulate other complimentary alleles from CWRs. This review will focus on present status of gene pool and species distribution, germplasm conservation, characterization and evaluation, problems associated with crop production, sources of target traits available in wild species, status of trait introgression in synthesizing new gene pool of chickpea along with progress made in chickpea genomics. --